Pendampingan Pembuatan Produk Jamu Herbal Masyarakat Desa Keleyan Kabupaten Bangkalan - Sri Wahyuningsih (LPPM Universitas Trunojoyo Madura, 2021)
During the Covid-19 pandemic since March 2019 in Indonesia, many parties must always be vigilant about the spread of this deadly virus, because many health workers and patients have died and its development continues to increase positively. While a cure for this deadly virus has not been found to date, prevention is preferable. The method of implementation carried out is that the author and the residents of Keleyan village, Socah sub-district, Bangkalan regency make herbal jamu under the brand